P172 Metabolic disorders with non-alcoholic fatty liver disease in people with inflammatory bowel disease. (30th January 2023) - Walker, C; Stapleton, E; Dempsey, M; Carroll, A; Connaughton, R; Breslin, N; McNamara, D; O'Donnell, S; Ryan, B; O'Connor, A
Abstract: Background: Globally rising rates of obesity and consequent metabolic diseases have been reflected in the inflammatory bowel disease (IBD) population. Non-alcohol fatty liver disease (NAFLD) is a common liver disorder associated with obesity, that occurs more frequently in people with IBD. Methods: A prospective single-centre cohort study. In total, we recruited 203 patients from our IBD service in a tertiary academic hospital. 7 participants were excluded due to later diagnosed non-NAFLD liver disease. Following informed consent, participants underwent a fibroscan for liver stiffness (LSM) and controlled attenuation parameter (CAP) measurement, and blood tests for HbA1c and fasting lipids. Basic demographics, past medical history, exercise measured on the Godin-Shepard Leisure Time Physical Activity Questionnaire, physical functioning on SF-36 Questionnaire, blood pressure, CAP and LSM were recorded. T-test and Fishers exact test were used to test for statistical significance as appropriate. Results: Of the 196 IBD patients included, 34.7% (n=68/196) had a healthy BMI, 34.7% (n=68/196) were overweight (BMI≥25-29.9), and 30.6% (n=60/196) were obese (BMI≥30). Overall, 16.3% (n=32) had a CAP score >294dB/m consistent with NAFLD, and 2.55% (n=5) had a LSM >8.1kPa consistent with fibrosis. When compared to those without NAFLD, those with NAFLD had higher BMIs, 26.9 vs 32.3 p<0.05. They also had a much higher incidence of diabetes 28.1% vs 0% p=0.0001, higher overall rates of abnormal HbA1C (≥6%), 21.9% (n=7/32) vs 6.4% (n=10/156) p=0.0121, and higher rates of abnormal HbA1c without a diagnosis of diabetes 13% (n=3/23) vs 6.45% (n=10/155) p=0.4043. Additionally, they had non-significant higher mean systolic blood pressure and higher rates of diagnosed hypertension. Compared to those without NAFLD, the NAFLD cohort had higher rates of diagnosed hypercholesterolaemia 34.4% (n=11/32) vs 15.3% (n25/163) p=0.022 and there were higher rates of elevated total cholesterol (>5mmol/L) in those not previously diagnosed with hypercholesterolaemia, 42.9% (n=9/21) vs 31.8% (n=47/148) p=0.3292. Participants with NAFLD also had lower exercise scores 17 vs 24.9 p=0.03543, and lower scores for physical functioning 71.9 vs 83.2 p=0.00676. Of particular note, they had more than double the 10-year risk of myocardial infarction or death determined by the Framingham risk scores for hard coronary heart disease, 2.48% vs 5.75%, p=0.00012. Conclusion: Our study shows that people with concurrent NAFLD and IBD have a significant cardiovascular risk profile. With increased awareness of this, metabolic syndrome conditions should be screened for and treatment initiated where appropriate, to decrease cardiovascular related mortality in this cohort.